Mining and analysis of dizziness adverse event signals in postoperative analgesia patients based on the FDA adverse event reporting system database - Zhou, Fengqi; He, Haiou; Gao, Jing; Zhang, Zhen (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to explore the association between drugs used in postoperative anesthesia patients and postoperative dizziness using the U.S. Food and Drug Administration’s Adverse Event Reporting System (FAERS) database, along with other risk factors for dizziness.MethodsUsing the FAERS database, we retrospectively analyzed dizziness cases reported between 2004 and the third quarter of 2023. We analyzed the relationship between drugs during postoperative anesthesia and the risk of postoperative dizziness, and conducted subgroup analysis according to age, sex and other factors. Signal detection was further performed using the reported odds ratio (ROR) method to identify medications significantly associated with an increased risk of postoperative dizziness.ResultsA total of 166,292 dizziness case reports were obtained, with 128 cases specifically related to postoperative analgesia. The number of dizziness reports has been increasing yearly, with a higher concentration of cases among individuals aged 18–85 years, predominantly in female patients. The analysis identified that amitriptyline, clonazepam, and ketamine were significantly associated with an increased risk of dizziness, with RORs of 34.91, 17.39, and 7.37, respectively. Subgroup analyses revealed variations in the relative risk of dizziness based on sex and age groups. Ketamine may be associated with higher risk of dizziness in the adult male subgroup.ConclusionThe results of this study suggest that specific medications used by patients with postoperative analgesia are associated with an increased risk of postoperative dizziness. Future studies should further validate this finding and explore other potential risk factors.